"Girls are not made of glass!": Barriers experienced by women in Norwegian Olympic boxing - Tjønndal, A. (Sociology of Sport Journal, 2019)
The marginalisation and exclusion of women in boxing has emerged as a severe global problem, threatening women`s democratic right to equal participation in sport (McCree, 2015; Godoy-Pressland, 2015). The following article is based on a qualitative study of women`s lived experiences as participants in boxing, either as coaches or as athletes. My theoretical point of departure is derived from an understanding of gender as a cultural code. The data material consists of interviews with Norwegian female boxing coaches and female boxers. The analysis in this study suggests that women, both inside and outside of the ring, are facing several obstacles to overcome and barriers to break. For instance, both female coaches and boxers struggle to be taken seriously in their sporting practices. For women coaches, a central challenge is being accepted and respected as `real` and capable coaches with valuable knowledge and experience in a male dominated sport. Women boxers on the other hand, are often subjected to unequal power relations with older male coaches. As expressed by the interviewed boxers, some men take advantage of these gendered power relations in terms of practices of exclusion, discrimination, and in some cases, sexual abuse.